Research Progress of TCM Treatment of Chronic Pharyngitis - Shao, Shuxin; Zhang, Xiong (Journal of Contemporary Medical Practice, 2024)
Chronic pharyngitis is a chronic inflammation of the pharyngeal mucosa, submucosa and lymphoid tissue. The main clinical symptoms are dry pharynx, itching, foreign body sensation in pharynx, cough, nausea and retching. It has the characteristics of long course of disease, easy recurrence, prolonged and difficult to cure. The etiology of chronic pharyngitis is complex and the symptoms are stubborn. At present, Western medicine treatment includes oral or nebulized inhalation of antibiotics to fight infection, nebulized inhalation of hormones, a large amount of vitamin supplement and comprehensive dietary intervention. Although there are many western medical treatment methods, they are mainly to improve local symptoms, with unstable conditions, more adverse reactions, and patients' compliance is not high. The treatment of traditional Chinese medicine is based on the fundamental and holistic treatment, which has considerable advantages in improving the symptoms of chronic pharyngitis, reducing recurrence and improving the quality of life of patients.